2012
DOI: 10.12688/f1000research.1-17.v1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying spatial priorities for protecting ecosystem services

Abstract: Priorities for protecting ecosystem services must be identified to ensure future human well-being. Approaches to broad-scale spatial prioritization of ecosystem services are becoming increasingly popular and are a vital precursor to identifying locations where further detailed analyses of the management of ecosystem services is required (e.g., examining trade-offs among management actions). Prioritization approaches often examine the spatial congruence between priorities for protecting ecosystem services and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 57 publications
0
27
0
1
Order By: Relevance
“…Despite the limitations of our study, some implications can be drawn for policies in Costa Rica. The positive correlations between carbon, biodiversity and local services makes it possible to develop conservation policies with synergies for multiple ES, as in other countries (Chan et al 2006;Turner et al 2007;Bai et al 2011;Egoh et al 2011;Luck et al 2012). According to our results, current conservation policy mechanisms in Costa Rica contribute to the delivery of multiple ES: protected areas provide high levels of carbon and water-related services, and PES areas provide high levels of biodiversity, carbon and scenic beauty.…”
Section: Policy Implicationsmentioning
confidence: 53%
See 2 more Smart Citations
“…Despite the limitations of our study, some implications can be drawn for policies in Costa Rica. The positive correlations between carbon, biodiversity and local services makes it possible to develop conservation policies with synergies for multiple ES, as in other countries (Chan et al 2006;Turner et al 2007;Bai et al 2011;Egoh et al 2011;Luck et al 2012). According to our results, current conservation policy mechanisms in Costa Rica contribute to the delivery of multiple ES: protected areas provide high levels of carbon and water-related services, and PES areas provide high levels of biodiversity, carbon and scenic beauty.…”
Section: Policy Implicationsmentioning
confidence: 53%
“…However the choice of the indicators was constrained by data availability, as in most ES mapping studies (Eigenbrod et al 2009;Bai et al 2011;Luck et al 2012). Biodiversity provision was derived from maps of species richness and endemism at the country scale.…”
Section: Strengths and Limitations Of The Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting ecosystem services in conservation planning may achieve many biodiversity targets under an attractive easy-to-sell umbrella of services, while at the same time improving the relevance of conservation plans to human wellbeing (Luck et al 2012). However, there is a still unresolved debate about the extent to which the components of biodiversity should correspond with ecosystem services provision (Chan et al 2011, Reyers et al 2012b, Schröter et al 2014b) and about the extent to which considering ecosystem services in decision-making matches with biodiversity conservation objectives.…”
Section: Planning For the Conservation And Management Of Ecosystem Sementioning
confidence: 99%
“…Schröter et al (2014a) found that including regulating and cultural ecosystem services shifts priority sites and increases the area of biodiversity conservation leading to additional conservation efforts, regarding higher opportunity costs and a larger area protected. New developments extend the practicality of spatial conservation planning tools for modeling multiple ecosystem services and optimizing potentially conflicting landuse requirements , Luck et al 2012). …”
Section: Planning For the Conservation And Management Of Ecosystem Sementioning
confidence: 99%